2019
DOI: 10.1088/1674-4926/40/10/101305
|View full text |Cite
|
Sign up to set email alerts
|

III–V compound materials and lasers on silicon

Abstract: Silicon-based photonic integration has attracted the interest of semiconductor scientists because it has high luminous efficiency and electron mobility. Breakthroughs have been made in silicon-based integrated lasers over the past few decades. Here we review three main methods of integration of III–V materials on Si, namely direct growth, bonding, and selective-area hetero-epitaxy. The III–V materials we introduced mainly include materials such as GaAs and InP. The lasers are mainly lasers of related communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Moreover, the D and G band values shied towards the lower values and the D/G intensity ratio (I D /I G ) decreasing from 0.927 to 0.908 showed that the GO had been well reduced to rGO. 45 The D/G intensity ratio (I D /I G ) roughly correlates to the amount of the graphene clusters and defects in the disordered carbon. 15 The I D /I G ratios of TiO 2 /GO-8 and TiO 2 /rGO nanocomposites are 0.927 and 0.908, respectively, both of which are higher than GO (0.896).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the D and G band values shied towards the lower values and the D/G intensity ratio (I D /I G ) decreasing from 0.927 to 0.908 showed that the GO had been well reduced to rGO. 45 The D/G intensity ratio (I D /I G ) roughly correlates to the amount of the graphene clusters and defects in the disordered carbon. 15 The I D /I G ratios of TiO 2 /GO-8 and TiO 2 /rGO nanocomposites are 0.927 and 0.908, respectively, both of which are higher than GO (0.896).…”
Section: Resultsmentioning
confidence: 99%
“…Several approaches such as direct growth of III–V on Si, III–V on lattice engineered substrates, and III–V on Ge–Si templates have been developed to integrate III–V compounds with the cutting-edge modern complementary metal oxide semiconductor (CMOS) technology. 21,22 Therefore, III–V semiconductor-based 2D ferroelectrics, if available, will reduce the barrier of integrating ferroelectric functionalities with silicon-based technology and lower the cost of commercialization.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Arsenide semiconductors, such as boron arsenide (BAs), 22 aluminum arsenide (AlAs), 23 gallium arsenide (GaAs), 5,24 and indium arsenide (InAs), 25 have emerged as promising candidates for vdWHs due to their favorable band alignments and light absorption properties. These materials belong to groups III-V of compound semiconductor materials [26][27][28][29] and play a vital role in making microwave devices, 30,31 Hall devices, 32 high-speed digital circuits, 33 lasers, 34,35 magneto-resistive devices, 7,35 and detectors. 36 Hexagonal BAs monolayer with a flat honeycomb structure like graphene has drawn attention as a potential photocatalyst for water splitting.…”
Section: Introductionmentioning
confidence: 99%